Parental Influence on Smoking Behavior in Teenagers - Nurhalimah, Nurhalimah; Putri, Fauziah Yuliana; Haryati, Omi; Banon, Endang; Nurlaela, Ela (Poltekkes Kemenkes Jakarta III, 2024)
Adolescence is a problematic and difficult period because it often gives rise to several problems that are difficult to overcome, such as drug and cigarette dependence. The proportion of smoking among teenagers aged less than 15 years is greater than among those aged above because teenagers tend to have a greater curiosity, so they are more likely to smoke than adults. Parents are one of the factors causing smoking behavior in teenagers, because parents are figures for their children, so if parents smoke, teenagers tend to imitate their parents' behavior. Parents who smoke significantly increase teenagers' tendency to smoke by 1.397 times compared to teenagers whose parents are not smokers. Smoking has a huge negative impact on teenagers. Knowing how much influence parents have on adolescent smoking behavior. This research uses quantitative methods, and analytical descriptive design with a cross-sectional approach. The research population was teenagers with smoking behavior, totaling 83 respondents. The sampling technique uses purposive sampling. The questionnaire used was created by researchers from modifications from various sources. There is a significant relationship between parental influence and smoking behavior in adolescents. With an OR of 2,824, this means that parents have a 2,824 times chance of causing smoking behavior in teenagers. There is a need to educate parents not to smoke at home and in front of their children.